Analisis distribusi pendapatan transporter online di Kota Jambi (studi kasus pengemudi gojek) - Ilham Praditya; Rosmeli Rosmeli; Selamet Rahmadi (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze the socio-economic characteristics and income distribution of gojek drivers in Jambi City. The data used is primary data. Data were collected through interviews and questionnaires to gojek drivers in Jambi City. The data were analyzed descriptively-quantitatively. The results of the study found that the income distribution of Gojek drivers in Jambi City was categorized as low inequality. This can be proven by the Gini Ratio of 0.14. At the same time, the position of the Lorenz Curve is located not far from the diagonal line